A Review of Cement Mortars Exposed to Elevated Temperatures - Faisal K. Abudel-Hussein; Zainab H. Mahdi; Marwan Samir Al-Shaikhli (Journal of Madenat Alelem University College, 2021)
Cement mortars are one of the popular composite materials that are used for various purposes in construction industries. Many investigations were conducted over the past few decades with the aim of enhancing its characteristics. Fire resistance is one of these important fields since fire is one of the most dangerous situations for buildings and it has many and different causes such as arson, electrical short circuit, lighting, etc. Therefore, the purpose of this paper is conducting a review of the previous studies on the mechanical properties of cement mortars subjected to elevated temperatures. These studies were examined and explained in a chronological narrative style. Researchers, in general, have inspected the influence of adding/replacing materials in cement mortars such as fly ash, superplasticizer, nanosilica, etc. Compressive and flexural strengths were the most examined parameters. In addition, cooling methods and their influence on fire resistance were also considered.